DIVERSITY OF FERN SPECIES (PTERIDOPHYTA) IN KEBUN RAYA BANUA BANJARBARU, SOUTH KALIMANTAN PROVINCE - Abdi Gusti, Muhammad; Prasetyo, Opik; Alifia Puspita Sari (Universitas Negeri Manado, 2025)
Ferns (Pteridophyta) are a group of Cryptogamae plants that play an important role in maintaining ecosystem balance and have the potential to be a source of biodiversity learning. This study aims to determine the diversity and evenness of fern species in the Kebun Raya Banua, Banjarbaru City, South Kalimantan Province, and to analyze the environmental factors that influence their existence. The research was conducted using an exploratory survey method with purposive sampling techniques at three observation stations. Diversity analysis was performed using the Shannon–Wiener Index (H’) and the evenness index (E). The results showed that there were 8 species of ferns belonging to 5 families, namely Asplenium nidus, Gleichenia linearis, Nephrolepis biserrata, Lygodium circinnatum, Davallia denticulata, Drynaria quercifolia, Adiantum raddianum, and Microsorum scolopendria, with a total of 62 individuals. The diversity index value H' = 1.894 is classified as moderate, while the evenness index value E = 0.56 indicates that species distribution is also moderate. These values indicate that the environmental conditions at Kebun Raya Banua are still relatively stable and support the growth of various types of ferns, with temperature, humidity, soil pH, and light intensity as important factors that influence diversity variation between observation stations.